Appreciating the silver lining: influence of holistic thinking on gratitude and positive reframing in the context of COVID-19 - Teo, Genevieve Wei Ning (Nanyang Technological University, 2023)
The COVID-19 pandemic has brought about huge changes across the world, with many experiencing negative impacts as a result. However, some have managed to see the silver lining amidst the negativity and even rose above and beyond to engage in charitable acts and to turn the pandemic into learning opportunities. We suspect that holistic thinking has a pivotal role to play in spurring one to positively reframe negative events and to both feel and express more gratitude in the context of the pandemic. To investigate this, 250 participants residing in Singapore were recruited via an online research crowdsourcing channel. Participants were primed to think more holistically by reading statements about holistic thinking, or less by reading statements unrelated to holistic thinking and rating them using a positive anchored scale. Gratitude was measured both as experienced gratitude using a rating scale and expressed gratitude via the sentiments expressed in gratitude notes and the number of words written by participants. Positive reframing was measured using a rating scale. Contrary to our hypothesis, holistic thinking did not elicit a greater sense of gratitude nor compel participants to express more positive sentiment and expend more effort in terms of the number of words written in gratitude notes than those in the neutral condition. In fact, those in the holistic thinking condition expressed less gratitude sentiment than those in the neutral condition. Plausible explanations for unexpected findings, implications and future directions are discussed.